On the presence of Daphnia galeata in Lake Orta (N. Italy) - Marina MANCA; Carla BONACINA; Jaromir SEDA; Roberta PISCIA (Journal of Limnology, 2006)
Lake Orta is a very interesting environment because of its history of heavy chronic pollution and biota re-colonization. It was the first deep lake in Italy in which allozyme techniques were used to investigate clonal diversity. In 1986, a newly established Daphnia obtusa population, able to colonize stressed environments, resulted composed by just one multilocus genotype, detected through an analysis of 27 different allozymes, fifteen of which active and stable for up to 12 generations. This result was interpreted as indicative of a colonization by a single clone, able to establish after a strong selection. This species was allochthonous for the lake, and in 1996 was replaced by a Daphnia longispina of the same morphotype as that originally described from its pelagic environment, the latter apparently remaining the only Daphnia species also in the lake’s littoral until 2001, i.e. until a regular sampling to monitor the lake was accomplished. During an accidental sampling in 2004, for detecting the occurrence and prevalence of parasites in Daphnia parental species and hybrids in several lakes located North and South of the Alps, Daphnia galeata was first found in Lake Orta’s pelagic environment, as revealed by morphological and allozyme analyses. Lake Orta zooplankton was then resampled in June 2006, to detect species as well as clonal composition of the Daphnia population, using the same techniques of morphotype and allozyme analyses. We expected to find low clone diversity and the occurrence of hybrids, whose success is enhanced in disturbed environments. Although preliminary, our results confirm that clone diversity Lake Orta’s Daphnia population is low, thus suggesting a recent colonization by D. galeata and providing evidence for a founder effect. In addition, the detection of the M variant at the AO locus, we interpret as a rare allele of D. galeata/D. longispina hybrids, perfectly fits the hypothesis of an enhancement of hybrid success in disturbed environments such as the once heavy polluted Lake Orta.